CUSTOMER LOYALTY: IMPROVE CUSTOMER RELATIONSHIP MANAGEMENT THAT IMPACT THE CUSTOMER SATISFACTION - Muh. Shadri Kahar Muang; Edi Indra Setiawan; Rikal Fajar Masati (Al-Amwal : Journal of Islamic Economic Law, 2020)
This study aims to determine the effect of customer relationship management consisting of people, processes, on customer satisfaction and loyalty in Palopo City . This study uses a quantitative research approach by examining specific populations or samples, sampling techniques are generally carried out randomly, collecting data using research instruments, statistical data analysis with the aim of testing hypotheses that have been set using Smart PLS 3.2.8 software . The results showed that the customer relationship management variable which consists of people, processes, and technology has a positive and significant impact on customer satisfaction. Customer relationship management consisting of people, processes, and technology has a positive and significant influence on customer loyalty, while satisfaction has a positive but not significant effect on customer loyalty. The indirect effect (mediation) shows that satisfaction can mediate the influence of customer relationship management consisting of people, processes, and technology on customer loyalty.